Analisis Pemahaman Wajib Pajak UMKM dan Kewajiban Perpajakan Penetapan Tarif UMKM di Pasar Bakti - Nurkhasanah; Muhammad Arief; Ahmad Sani (Forum Kerjasama Pendidikan Tinggi, 2025)
This research aims to determine the understanding of taxpayers as well as rates setting on MSME players in Pasar Bakti Medan City. In conducting this research, a qualitative descriptive method was used. While data collection was carried out using observation and interview techniques as many 10 MSME merchants and documentation, namely the financial statements of MSME merchants. From the results of this research, it can be concluded that MSME merchants in Pasar Bakti Kota Medan do not understand paying taxes and do not know the tax rates and Government Regulation No. 46 of 2013 and the new Government Regulation No. 23 of 2018 also MSME taxpayers do not know. Understanding of MSME taxpayers in Pasar Bakti Kota Medan on general provisions and tax procedures is still low. The level of awareness of MSME actors of tax obligations is one of the factors causing non-compliance in carrying out tax payment obligations. The understanding of MSME taxpayers in Pasar Bakti Medan City is still low with the existence of Government Regulation No. 46 of 2013 on the basis of the imposition of a rate of 1% of gross turnover. Realisation that is still not fully implemented as a whole. The lack of socialisation to the community and taxpayers (MSME merchants) is one of the factors inhibiting the implementation of this regulation as well as Government Regulation No. 23 of 2018 which the technical implementation is not yet clearly known